Something to live for the music of Billy Strayhorn - Leur, Walter van de.; Oxford eBooks (New York ; Oxford : Oxford University Press, 2002)
Walter van de Leur traces the origins of Billy Strayhorn's music, with its roots in European and American idioms, and uncovers hitherto unknown works that cast a new light on his development as a composer and orchestrator.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Strayhorn, Billy -- Criticism and interpretation; Ellington, Duke, -- 1899-1974 -- Criticism and interpretation; Electronic books